Petrographic and chemical analyses of sherds from the Kurin Lapita site (Loyalty Islands, New Caledonia), ca. 3000–2700 BP. (October 2020) - Chiu, Scarlett; Killick, David; Sand, Christophe; Su, Yu-yin; Ferguson, Jeffrey R.; Chao, Jiunn-Hsing
Highlights: We report analyses of Lapita potsherds (3000–2700) BP from the Loyalty Islands. Our results do not demonstrate the colonization of Loyalty Islands from Vanuatu. Our results are compatible with the "leapfrogging" model of initial Lapita colonization. Abstract: As part of a wider study of the transfer of Lapita pottery into and within New Caledonia, we studied a sample of Lapita sherds from the site of Kurin on Maré, Loyalty Islands, New Caledonia. The Loyalty Islands lie between the Vanuatu island chain and the rest of New Caledonia, so it has been suggested that they may have been the first part of New Caledonia to have been colonized during the initial Lapita expansion. We examined 28 sherds by optical petrography, and compared these to archived thin sections of Lapita pottery from the islands of Erromango and Efate in Vanuatu. We also made chemical analyses by neutron activation analysis (INAA) of 11 of these 28 sherds, and later reanalyzed these 11, and 12 more, by inductively-coupled plasma (ICP) analysis as part of the analysis of 329 sherds from throughout New Caledonia. We find no evidence in this sample for the transfer of Lapita pottery from Vanuatu to the Loyalty Islands; the only demonstrably exotic pots are 5 sherds from the main island (Grande Terre) of New Caledonia. Our results offer some support to the view that the initial Lapita expansion was not a continuous wave of advance, but a discontinuous "leapfrogging" process that initially bypassed some island chains. We also note evidence for the existence of at least two mutually exclusive networks of exchange of Lapita pottery in New Caledonia after the initial colonization of the region.